Homenaje al ateneísta Blas Infante / [presentación de Enrique Barrero González] - Barrero González, EnriqueChaves González, ManuelEscuredo, Rafael (1944-) Rubiales Torrejón, Amparo
Contiene textos de Manuel Chaves González, Rafael Escuredo Rodríguez y Amparo Rubiales Torrejón